PSYCHOSOMATICS OF TUBERCULOSIS: BIBLIOMETRIC APPROACH - S. V. Kandrychyn (Туберкулез и болезни лёгких)
The article presents the analysis of a number of publications devoted to psychosomatics of tuberculosis in PubMed/Medline for the period from 1946 to 2016. The majority of publications devoted to this issue were published indicates after the war, and after that period researchers paid less attention to this topic. An opinion is expressed that this descending number of publications indicates of some problems in the field of socially oriented preventive medicine.